On "rusting" money: Silvio Gesell's Schwundgeld reconsidered - Günther Rehme (Technische Universität Darmstadt, Department of Law and Economics, 2018)
Silvio Gesell hypothesized that money depreciation is economically and socially beneficial, ideas that have often been contended. Here I analyze that in a Sidrauski model in which households additionally have a "love of wealth"-motive. It is shown Gesell's claims may be valid in a demand-determined, short-run equilibrium and why money depreciation overcomes the zero lower bound on nominal interest rates. However, for a typical long-run equilibrium introducing money depreciation in isolation may be bad. But money depreciation, when coupled with expansionary monetary policy, is a necessary condition for a positive Mundell-Tobin effect on long-run real variables and so creates wealth in the model. It is found that this also holds in the transition to the long-run equilibrium. Hence, the spirit of Gesell's hypotheses can be verified for a plausible, long-run environment.
urn:nbn:de:tuda-tuprints-75388
Keywords: E1; E5; O4; 330; Economic Performance; Depreciating Money; Zero Lower Bound; Demonetization; Love of Wealth